Enhancement of the University of the Philippines Mindanao online student and teacher locator (E-UPMOSTL) - Peña, Hazel Serohijos dela. (2008)
Enhancement of the University Online Student and Teacher Locator is made for the realization of the existing system of Mallari (2005). Its goal of locating students and teachers through the Internet is the goal of this software. Timetable of the students and faculty were used to know of their whereabouts inside the university. The new feature of this system is the adding of students and teachers? information from excel file and importing it to the database. This can only be done by the administrator apart from having the sole authority to add or make changes on the students and teachers information and subject schedule. The differences between the two other users (faculty and students) are the following: faculty can post announcements but the students are not allowed. Students can only send assignments and teachers can upload them. School year and semester must be included in adding subjects to make sure that in searching them, they are in the proper academic year and semester, this system is a web-based application; therefore, Internet is highly needed. Additional studies can also be made to make this software more sophisticated. Maintenance of the system is still necessary for data accuracy
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2008
Keywords: Information system; Online student locator; Online teacher locator